Demographic characteristics of trauma patients of the Emergency Department of Marmara University Hospital [Marmara Üni̇versi̇tesi̇ Hastanesi̇ Aci̇l Servi̇si̇ne başvuran travma hastalarinin demografi̇k özelli̇kleri̇] - (:unkn) unknown (My University, 2005)
Objective: This study aims to describe the characteristics of trauma patients admitted to the Marmara University Hospital, Department of Emergency Medicine. Materials and Methods: Patients admitted to our ED between 1st January - 31st December 2004 were retrospectively analysed from the admission charts and patient files, 636 cases met the inclusion criteria. Age, sex, trauma properties, admission, disposition, mortality and morbidity frequencies have been calculated. Cases have been divided into local and multiple trauma groups. Also the admission frequencies and the factors affecting decision for admission have been searched. Chi-square and Fischer's Exact tests were used in statistical analysis, p<0.05 accepted to be statistically significant. Results: Six hundred and thirty six trauma patients have met the criterion to be included in the analysis. Most of the cases were men (67%) and the median age was 42. Statistically there was no difference between the number of the local and multiple trauma cases. Hospitalization rates of multitrauma patients was significantly higher. The most frequent mechanism of trauma was falls. Rates of associated diseases were significantly higher in our patients. Most patients were admitted between April and June 2004. Conclusion: Dispersion of the cases and demographics of the patients seemed to resemble the conclusions that have been reached by the other emergency medicine departments of the universities in other cities, but our patients were older and had more comorbid diseases when compared with the state hospitals in our city. Leading cause of trauma was falls in our clinic in 2004.
Keywords: Demographics; Patient profile; Trauma